IMPLEMENTASI MANAJEMEN PESERTA DIDIK DALAM MEMBENTUK KARAKTER RELIGIUS SISWA - Adah Aliyah; Muchammad Erihadiana; Muhibinsyah Muhibinsyah (Universitas Islam Madura, 2023)
The blurring of identity is an interesting phenomenon in itself for the world of education, it is not easy to filter out negative culture, moral degradation, corruption, discrimination, violence, religious conflict is increasingly prevalent, this is caused by undefined characters in the world of education, so it is a strong reason for research. . This study uses a descriptive qualitative research approach. Collecting data with interviews, observation and documentation. The data analysis with triangulation. The findings are organizing counseling and coaching programs, conditioning students, providing student services, recording students who violate the code of ethics, monitoring and making student MOUs with school. The implementation process is to divide student council job descriptions, always control religious activities, set a good example, and create a positive climate, involve students in religious activities and condition and inform parents of students regarding student development. The implication of this research activity is that the management of religious character formation is important to get serious attention for education managers, because religious character will produce students who are honest, tenacious and creative so that they become qualified and if they become leaders, they will become good leaders. Honest, Trustworthy and persistent in work.